IMPROVEMENT OF COUNTERING ILLEGAL FINANCIAL TRANSACTIONS WITH PAYMENT CARDS - Bozhenko, Victoria; Kildei, Anastasiia; Lieonov, Hlib (Socio-economic relations in the digital society, 2022)
The article summarizes the arguments and counter-arguments in the scientific debate on the relationship between cyber fraud and financial crime. The main purpose of the study is to improve the system of counteraction to illegal financial transactions using payment cards. The urgency of solving this scientific problem is due to the fact that increasing online payments, and rising the volume of non-cash payments using bank payment cards creates conditions for various forms of fraud that require legal regulation and identifying possible ways to combat such crimes. The study found that the degree of fraud is directly influenced by factors such as a low level of digital and financial literacy; a lack of a standardized customer authentication system; a large amount of financial and personnel data; relatively low efficiency of the information security control system of banks. According to the analysis of the current state and trends in the financial sector, the following subsystems have been identified that make up the general system of combating fraud with bank payments, such as banking management (functional subsystem), information and communication technology management (technological subsystem), regulatory support legislative subsystem) and increasing the level of digital and financial literacy of consumers of financial services (educational subsystem). The results of the study have practical value for the management of financial institutions to improve the system of combating illegal financial transactions using payment cards, namely the creation of separate bodies for analysis and regulation of fraud in the banking sector, strengthening responsibility for fraud at the legislative level, establishing a single, development of open banking system.
Keywords: fraud; payment instruments; bank cards; financial crimes